PROBLEMS OF TECHNOLOGY OF THE OILY PAINTING DURING THE PROSECUTION OF STANKOVOY ONE BY A PICTURE - Mishurovsky, V.V. (Pedagogy of Higher and Secondary Education, 2022)
In the article is examined the issue professional preparation o f teacher graphic arts.